Implementation of the concept of green logistics reffering to it applications for road freight transport enterprises - Vasiliauskas, Aidas Vasilis; Zinkevičiūtė, Virgilija; Šimonytė, Eglė (Business: Theory and Practice, 2013)
The article examines a scientific and practical problem concerning the ability to implement a concept of green logistics with reference to IT applications for Lithuanian road freight transport enterprises. A scientific discussion develops the relation between the concept of green logistics and the principles of sustainable development. The paper analyses the main problems of green logistics and IT employment in the sector of Lithuanian road freight transport enterprises and focuses on the elaborated model representing a set of IT applications necessary to achieve the goals of green logistics in the road freight transport enterprise.